Historical, Technological, Biochemical, and Microbiological Aspects of Pastirma, an Ethnic Meat Product from Asia to Anatolia: A Narrative Literature Review - GÜNGÖREN, Alper (MDPI AG, 2024)
Pastirma is an ethnic meat product derived from dry curing, drying, and pressing the whole muscles of cattle and buffalo and coating them with a special paste containing fenugreek seed flour, garlic, milled red capia pepper, and water. In this narrative literature review, the history of pastirma, its definition and classification, detailed production steps, composition and yield, chemical and microbiological properties, pastirma fraud, and customer concerns are mentioned. In this narrative review, relevant studies were identified by searching Scopus, Science Direct, Web of Science, Trdizin, and Google Scholar, including articles, online reports, books, and electronic books in English or Turkish. The keywords “pastirma, cemen, cemening, cemen paste, fenugreek” were used. The results of this review indicate that future studies on pastirma may focus on the related cultural aspects, the elimination of unpleasant odor from fenugreek, providing a detailed grading guide, the histological and chemical effects of pressing meat parts, the kinetics of drying, osmotic dehydration, and developing new starter combinations. Additionally, this is the first article to provide information on grading and food fraud in pastirma.